Introduction to protein architecture - Branden, Carl (Oxford University Press, 2001)
Written in a clear and engaging style, and profusely illustrated with superb computer graphics, Introduction to Protein Architecture is a textbook for second and third year undergraduate students and beginning post-graduate students, and will be of interest to all biological and medical scientists whose work touches on proteins.